Attitude towards the Scriptures of other Religions: A Gandhian Model - A Pushparajan (Journal of Dharma, 1982)
Holy Scriptures are the bedrock of all great religions. Religions like Judaism, Christianity and Islam are rightly called ’religions of the Book.’ Even those religions which do not have one specific book for their scriptures depend ultimately on some sacred texts considered authoritative. Now, often enough, the claims of one scripture con- flict with those of another. This can give rise to a number of prob- lems in a multi-religious context. How should one reconcile the claims of one’s own religious scriptures with the counter-claims of other religious scriptures? What sort of attitude should one have towards the scriptures of other religions? Should one read them at all? If so, how should one interpret them? If not, is one to simply ignore them or/and undervalue them? For answering these and similar ques- tions, it seems to me, Gandhi presents the most plausible model